Part-Time α-Secretases: The Functional Biology of ADAM 9, 10 and 17 - Deuss, Miriam; Reiss, Karina; Hartmann, Dieter (Current Alzheimer Research, 2008)
Disintegrin metalloproteases of the ADAM family form a large (at present > 40 members in mammals) family of multidomain membrane proteins that in their ectodomain combine a cystein-rich, disintegrin and a zinc metalloprotease domain. Via their metalloprotease domain, ADAMs are often implicated in ectodomain shedding, either to release e.g. growth factors or to initiate further intracellular signalling via regulated intramembrane proteolysis. Mainly based upon overexpression studies in vehicle cells, three of them, ADAMs 9, 10 and 17, have been proposed to act as α-secretases for amyloid precursor protein (APP). It is striking thereby that this role has since then remained somewhat ill-defined, as APP processing in ADAM9 deficient neurons is unaltered, and also ADAM10 deficient murine embryonic fibroblasts exhibit at best a highly variable reduction in α-secretase activity. However, during the past years, numerous other substrates have been linked to all three sheddases, the cleavage of which in some cases appears to be strikingly more important for the organism than APP processing. Most notably, the perinatally lethal phenotype of ADAM17 knockout mice is dominated by a loss of growth factor shedding, while the even earlier fatal effects of ADAM10 deficiency exhibit key features of disabled Notch signalling and possibly also cadherin processing defects. In this review, we will summarize the published data on the “non-APP” functions of all three ADAMs, the further evaluation of which may be crucial when attempting to treat Alzheimer's Disease by increasing their expression and/or activity. As the knockouts of ADAM10 and ADAM17 are only informative for their roles in (early) development, while a number of recently assigned new substrates play crucial roles in the normal and/or diseased adult organism as well, work on conditional knockout models will be crucial to fully characterize both the full functional portfolio of (candidate) α-secretases as well as their clinical relevance, which may go way beyond Alzheimer's Disease.